2007
DOI: 10.1037/1528-3542.7.3.478
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and sensitivity to gaze direction in emotionally expressive faces.

Abstract: This study investigated the role of neutral, happy, fearful, and angry facial expressions in enhancing orienting to the direction of eye gaze. Photographs of faces with either direct or averted gaze were presented. A target letter (T or L) appeared unpredictably to the left or the right of the face, either 300 ms or 700 ms after gaze direction changed. Response times were faster in congruent conditions (i.e., when the eyes gazed toward the target) relative to incongruent conditions (when the eyes gazed away fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
202
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 180 publications
(227 citation statements)
references
References 54 publications
22
202
3
Order By: Relevance
“…For each subject, only RTs within 2.5 standard deviations from the mean of each condition were kept in the mean RT calculation (Van Selst & Jolicoeur, 1994). On average, less than 7.5% of trials were excluded per condition in each experiment.It has been shown that a face gazing directly at the participant triggers slower response times than the same face looking to the side, especially when displaying a threatening facial expression (Fox et al, 2007;Georgiou et al, 2005;Mathews et al 2003), which is consistent with the idea that different processes underlie the perception of direct and averted gaze (George, Driver, & Dolan, 2001). Because direct gaze seems to capture attention to a larger extent than averted gaze (Senju & Hasegawa, 2005), we followed what has been done in previous gaze-orienting studies (Bayless et al, 2011;Fox et al, 2007;Mathews et al 2003) and analyzed direct gaze separately from averted gaze.…”
supporting
confidence: 73%
See 4 more Smart Citations
“…For each subject, only RTs within 2.5 standard deviations from the mean of each condition were kept in the mean RT calculation (Van Selst & Jolicoeur, 1994). On average, less than 7.5% of trials were excluded per condition in each experiment.It has been shown that a face gazing directly at the participant triggers slower response times than the same face looking to the side, especially when displaying a threatening facial expression (Fox et al, 2007;Georgiou et al, 2005;Mathews et al 2003), which is consistent with the idea that different processes underlie the perception of direct and averted gaze (George, Driver, & Dolan, 2001). Because direct gaze seems to capture attention to a larger extent than averted gaze (Senju & Hasegawa, 2005), we followed what has been done in previous gaze-orienting studies (Bayless et al, 2011;Fox et al, 2007;Mathews et al 2003) and analyzed direct gaze separately from averted gaze.…”
supporting
confidence: 73%
“…Because direct gaze seems to capture attention to a larger extent than averted gaze (Senju & Hasegawa, 2005), we followed what has been done in previous gaze-orienting studies (Bayless et al, 2011;Fox et al, 2007;Mathews et al 2003) and analyzed direct gaze separately from averted gaze.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations